Patient Satisfaction of BPJS Users In Inpatients At Aisyiyah Bojonegoro Hospital - Melinda Husni Kasari; Ana Kumalasari; Dilbarova Malika Rahimjon (Universitas Bojonegoro, 2026)
This study aims to measure the level of satisfaction of BPJS Kesehatan patients using inpatient services at Aisyiyah Bojonegoro Hospital. The type of research employed is descriptive, with a quantitative approach, and utilizes a questionnaire as the primary instrument to measure patient satisfaction levels among 278 respondents. The research instrument is based on nine elements outlined in Permen PAN-RB No. 14 of 2017. The data analysis techniques used are the Community Satisfaction Index (CSI) and Importance-Performance Analysis (IPA). The results of the study indicate that the CSI score falls into the “Good” category with a score of 81.96. However, the IPA analysis identified several service elements in Quadrant I (high priority for improvement), such as requirements, systems, mechanisms, and procedures; service time; staff behavior; facilities and infrastructure; complaint handling; and suggestions and feedback. Other elements, like staff competence, were in Quadrant II (to be maintained). Meanwhile, elements such as costs or fees were in Quadrant III (low priority). Additionally, elements such as product specifications for the type of service provided were in Quadrant IV (excessive). This study recommends that the hospital conduct ongoing evaluations and improvements based on the complaints raised by respondents. If improvements are implemented, this will enhance patient satisfaction, particularly among BPJS Health patients, in inpatient services overall.